Substansi Pendidikan Karakter dalam Kitab Amsal: Implementasi dalam Pengasuhan Anak - Sherly Mudak; Anre Rasi; Sumarno Sumarno; Yusmaliani Yusmaliani; Agyamiyarsi Agyamiyarsi (Jurnal Arrabona, 2024)
This article will discuss how Christian parents can integrate the character education values found in the Book of Proverbs into today's parenting. Using the qualitative research method of content analysis, this article will analyze various relevant verses from the Book of Proverbs and apply these concepts in the context of children's character education. This study aims to help Christian parents understand how to guide their children to develop a solid personality rooted in biblical principles.